Adaptation of thoracic and lumbar curvature and spinal muscle activity under changing gravity - Meinke, Anita; Baez, Alessandro Longhi; Wiesmann, Niklas; Ullrich, Oliver; Green, David A.; Egli, Marcel; Swanenburg, Jaap (Frontiers in Physiology, 2025)
IntroductionThe effect of micro-gravity on the lumbar and in particular thoracic regions is poorly understood. The aim of this study was to evaluate spinal curvature across the lumbar and thoracic region, and extensor muscle activity during acute micro-gravity and hyper-gravity induced by parabolic flight. In addition, the association between our proxy measure of spinal curvature, and extensor muscle activity in micro-gravity was investigated.MethodsDuring two ESA parabolic flight campaigns, 18 participants (8 female; 33 ± 11 years) were measured under earth-gravity, micro-gravity and hyper-gravity conditions. Spinal curvature was assessed using “spinal curvature backpacks” equipped with 15 laser distance sensors to measure the distance between the backpack and the subject’s back. Change in the area enclosed between the back and the backpack was used to measure change in spinal curvature. Muscle activity of the erector spinae (in 4 locations) and multifidus muscles (1 location) was assessed using surface electromyography transmitters. In addition, the spearmen correlation between muscle activity and spinal curvature in micro-gravity was investigated.ResultsSpinal flattening was observed during micro-gravity exposure, with changes most pronounced in the upper lumbar and lower thoracic spine. Mean-normalized area between the back and backpack decreased significantly in micro-gravity compared to earth-gravity (p = 0.001), but not during hyper-gravity (p = 1.00). The erector spinae responded heterogeneously to different gravity conditions across different assessment sites. Multifidus activity at L5 and erector spinae activity at L4 significantly decreased in micro-gravity compared to earth-gravity and hyper-gravity (p’s <= 0.01) and correlated with spinal flattening (ρ = 0.69, p = 0.004; ρ = 0.67, p = 0.030).Discussion/ConclusionParabolic flight-induced gravity changes caused upper lumbar and lower thoracic spine flattening in micro-g, while spinal curvature remained unchanged in hyper-g. In micro-g, Multifidus (L5) and Erector Spinae (L4) activity decreased, while in hyper-g, increased ES activity was observed at the upper middle transmitter. The maintained curvature and targeted muscle activation in hyper-g demonstrate protective mechanisms against increased axial loading, crucial for posture and injury prevention in both terrestrial and space environments. The spinal and muscular changes in micro-g indicate the need for targeted countermeasures during spaceflight, warranting comprehensive assessment in future research.EthicsFrench “EST-III” (Nr-ID-RCB: 2022-A01696-37).